Design of Linear Multivariable Feedback Control Systems : The Wiener–Hopf Approach using Transforms and Spectral Factorization /: The Wiener–Hopf Approach using Transforms and Spectral Factorization. (2020) - Bongiorno Jr., Joseph J; Park, Kiheon
No abstract available